Control of excision frequency of maize transposable element Ds in Petunia protoplasts. - Becker, D (1992)
The complete coding region of maize transposable element Ac and truncated but active derivatives of it were placed under the control of promoters of different strength and tested for the ability to excise transposable element Ds from a beta-glucuronidase reporter gene in a cotransfection assay in Petunia protoplasts. The highest excision values (5% of the protoplasts able to express the beta-glucuronidase gene in a control experiment) were observed with a truncated version of the Ac coding region under the control of the 2' promoter. The weak Ac promoter is sufficient to give rise to excision values not much lower than those found with much stronger promoters such as the 2' and nos promoters. A decrease in excision frequency was observed when translation of the Ac coding region was hindered by out-of-frame ATG codons in addition to the use of weak promoters. Increasing the level of Ac transposase thus does not seem to be sufficient to raise the level of Ds excision observed in this system and possibly also in maize. Therefore another factor limits the excision of Ds elements. Previously, it was reported that in tobacco cells the deletion of Ds sequence between base pairs 186 and 245 led to a decrease of the Ds excision frequency by the full-length but not by the truncated Ac product. In the Petunia assay system, however, deletion of these sequences decreased the excision rate with both the full length and the truncated Ac coding region. A cDNA construct was found similarly active as the corresponding genomic DNA.